Sewage sludge does not induce genotoxicity and carcinogenesis - Paula Regina Pereira Silva; Luis Fernando Barbisan; Maria Lúcia Zaidan Dagli; Paulo Hilário Nascimento Saldiva (Genetics and Molecular Biology, 2012)
Through a series of experiments, the genotoxic/mutagenic and carcinogenic potential of sewage sludge was assessed. Male Wistar rats were randomly assigned to four groups: Group 1 - negative control; Group 2 - liver carcinogenesis initiated by diethylnitrosamine (DEN; 200 mg/kg i.p.); Group 3 and G4- liver carcinogenesis initiated by DEN and fed 10,000 ppm or 50,000 ppm of sewage sludge. The animals were submitted to a 70% partial hepatectomy at the 3rd week. Livers were processed for routine histological analysis and immunohistochemistry, in order to detect glutathione S-transferase positive altered hepatocyte foci (GST-P+ AHF). Peripheral blood samples for the comet assay were obtained from the periorbital plexus immediately prior to sacrificing. Polychromatic erythrocytes (PCEs) were analyzed in femoral bone-marrow smears, and the frequencies of those micronucleated (MNPCEs) registered. There was no sewage-sludge-induced increase in frequency of either DNA damage in peripheral blood leucocytes, or MNPCEs in the femoral bone marrow. Also, there was no increase in the levels of DNA damage, in the frequency of MNPCEs, and in the development of GST-P AHF when compared with the respective control group.